Personal and food hygiene practices of subsistence food vendors operating in Kano metropolis, northwestern Nigeria - Umar Muhammad Lawan,; Zubairu Iliyasu,; Sanusi Abubakar,; Auwal Umar Gajida,; Ahmad Abdussalam, (Universiti Kebangsaan Malaysia, 2015)
Background: Foodborne diseases are on the increase throughout the world due to poor attention given to personal and food hygiene measures by both lawmakers and people in charge of food preparation, especially in the developing countries. Objective: To examine the knowledge and practices of food vendors operating in urban Kano on personal and food hygiene. Materials and Methods: We used a descriptive cross-sectional design to study a random sample of 380 food vendors in Kano metropolis. Data were collected using pretested interviewer administered semi-structured questionnaire. Data were analyzed using Epi Infos software, version 3.5.1. Results: The mean age of the food vendors was 27.78 ± 7.63 years. The majority (61.1%) of them were men (53.2%), married (61.8%), and had at least secondary education (51.1%). More than two-thirds (89.7%) had fair knowledge of personal hygiene, although there were deficiencies in some of the key hygiene areas, but 62.4% and 36.6% had good and fair knowledge of food hygiene, respectively. Most of the food vendors had good practices of personal hygiene (93.2%). Paradoxically, only 17.1% had good practice of food hygiene. Furthermore, more than half (54.2%) showed bad workplace hygiene practices. Conclusion: Food vendors operating in Kano generally knew about personal and food hygiene, but this was not reflected in their hygienic practices. It is the statutory responsibility of the environmental health officers to safeguard and implement food hygiene laws in Nigeria. But despite the available structure and personnel at the local government area level, the laws are still inactive. The health authorities at the state and federal levels should empower the environmental health officers with the necessary policy and logistic support they require to fully implement the laws in Kano and Nigeria as a whole. The laws should also be reviewed to ensure more severe penalty for offenders.